Rapid Determination of Microbial Quinones using Supercritical CO2 Extraction - Faisal, Muhammad; Irvan, Irvan; Atsuta, Yoichi; Daimon, Hiroyuki; Fujie, Koichi (Jurnal Rekayasa Kimia & Lingkungan, 2006)
The supercritical CO2 extraction of microbial quinones from activated sludge samples obtained from various activated sludge was investigated and compared to the conventional method using organic solvent extraction. The extraction was carried out in a supercritical fluid extraction (SFE) system in the temperature range of 25 to75 oC and the pressure up to 30 MPa. Different extraction conditions, such as the temperature, pressure, extraction time and modifier were employed to maximize the SFE efficiency. Significant amount of microbial quinones (ubiquinones and menaquinones) could be extracted rapidly with supercritical CO2. Results on the value of diversity and dissimilarity suggested that the SFE with supercritical CO2 extraction was a reliable technique for quinones extraction.